2020
DOI: 10.1016/j.chb.2020.106424
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and digital inequalities: Reciprocal impacts and mitigation strategies

Abstract: With more than three billion people in isolation, the status of digital spaces is switching from an amenity to a necessity, as they become not only the main way to access information and services, but also one of the only remaining vectors for economic, educational, and leisure activities as well as for social interactions to take place. However, not all are equals in terms of access to networks or connected devices, or when it comes to the skills required to navigate computerized spaces optimally. Digital ine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
695
1
64

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 864 publications
(776 citation statements)
references
References 50 publications
16
695
1
64
Order By: Relevance
“…Prior to the COVID-19 pandemic, digital exclusion through reduced access to infrastructure and digital literacy had been viewed as key social determinant of health and national commitments had been made to target the issue 12 . Whilst our nding of digital inequality within the study population is not novel itself, we contribute to increasing evidence suggesting that digital inequality also potentiates vulnerability to the pandemic, thereby further increasing health inequalities 13 .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Prior to the COVID-19 pandemic, digital exclusion through reduced access to infrastructure and digital literacy had been viewed as key social determinant of health and national commitments had been made to target the issue 12 . Whilst our nding of digital inequality within the study population is not novel itself, we contribute to increasing evidence suggesting that digital inequality also potentiates vulnerability to the pandemic, thereby further increasing health inequalities 13 .…”
Section: Discussionmentioning
confidence: 82%
“…Whilst digital health technologies can improve the speed, reach and cost of many traditional public health measures, there are also speci c barriers to their e cacy; ownership of suitable hardware, internet access and digital literacy can greatly impact effective coverage across population groups 11 . Crucially, these three factors, which form the concept of 'digital inclusion' 12 , are considered to be important social determinants of health in themselves 13 . Research has demonstrated that groups who are at the highest risk of digital exclusion 14 are the elderly, those of Black and South Asian ethnic origin, those from deprived areas and those with low educational attainment; the same groups who suffer from the poorest COVID-19 health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A list open source data sets on the Kaggle can be found at. 18 A crowd-sourced list of open access COVID-19 projects can be found at. 19…”
Section: X-raymentioning
confidence: 99%
“…Although digital technologies have significantly aided the combat against COVID-19, they have also provided the ground for vulnerabilities that can be exploited in terms of social behaviors [120]. Fake news/misinformation sharing on social media platforms [15], racist hatred [16], propaganda (against 5G technologies and governments) [17], and online financial scams [18] are few forms of digital platform exploitation in COVID-19 pandemic. Fake news and rumors have been spread about lock-downs policies, over-crowded places, and death cases on social media platforms.…”
Section: Misuse Of Digital Technologiesmentioning
confidence: 99%
See 1 more Smart Citation